Application of ELECTRE Method for Selection of Diet Instant Noodles - Hugo, Veronika Novia; Sekarsari, Yulia Ayu; Kencana Putri, Ida Ayu Putu Calista; J.A, Qurrotul Ainia; Sudipa, I Gede Iwan (Yayasan Sraddha Panca Widya Nusantara, 2025)
Healthy eating is becoming increasingly important, particularly among university students who often prefer convenient foods like instant noodles. However, not all instant noodles provide suitable nutritional content for dieting. This study aims to determine the best instant noodles for diet purposes using the ELECTRE (Elimination and Choice Expressing Reality) method, a multi-criteria decision- making approach. Data were collected from INSTIKI students via a questionnaire that covered criteria such as calorie content, fiber, fat, price, and taste. The ELECTRE method was then applied to analyze the data based on predetermined preferences and criteria weightings. Results identified the most suitable instant noodles for dietary needs, ranked highest in the ELECTRE analysis. This study aims to guide consumers in making healthier choices and provide insights for manufacturers to improve product quality.